Genetic Parameters and Genome-Wide Association Studies for Anti-Mullerian Hormone Levels and Antral Follicle Populations Measured After Estrus Synchronization in Nellore Cattle - Grigoletto, Lais; Almeida Santana, Miguel Henrique; Bressan, Fabiana Fernandes; Eler, Joanir Pereira; Gouveia Nogueira, Marcelo Fabio [UNESP]; Kadarmideen, Haja N.; Baruselli, Pietro Sampaio; Sterman Ferraz, Jose Bento; Brito, Luiz F. (Mdpi, 2020)
Simple Summary Reproductive performance has direct economic implications on the beef cattle industry. The majority of Zebu breeds (e.g., Nellore;Bos taurus indicus) have poor reproductive performance compared to other cattle breeds. In this context, genetic progress can be achieved for fertility and reproduction through the use of genomic selection for indicator variables that efficiently assess the biological mechanisms underlying cattle fertility. Therefore, this study aimed to estimate genetic parameters (heritability and genetic correlations) and identify candidate genes associated with anti-Mullerian hormone levels (AMH) and antral follicle populations measured after estrous synchronization (AFP) in Nellore cattle. Our findings indicate that measuring circulating AMH in Nellore cattle enables the identification of animals with high genetic merit for superovulatory responses, as well as early selection of the best oocyte donors for in vitro embryo production. Both traits are heritable and influenced by a large number of important genes. Therefore, AMH and AFP can be used as indicator traits to genetically improve fertility rates in Nellore cattle and to identify better oocyte donors. Reproductive efficiency plays a major role in the long-term sustainability of livestock industries and can be improved through genetic and genomic selection. This study aimed to estimate genetic parameters (heritability and genetic correlation) and identify genomic regions and candidate genes associated with anti-Mullerian hormone levels (AMH) and antral follicle populations measured after estrous synchronization (AFP) in Nellore cattle. The datasets included phenotypic records for 1099 and 289 Nellore females for AFP and AMH, respectively, high-density single nucleotide polymorphism (SNP) genotypes for 944 animals, and 4129 individuals in the pedigree. The heritability estimates for AMH and AFP were 0.28 +/- 0.07 and 0.30 +/- 0.09, and the traits were highly and positively genetically correlated (r(G)= 0.81 +/- 0.02). These findings indicated that these traits can be improved through selective breeding, and substantial indirect genetic gains are expected by selecting for only one of the two traits. A total of 31 genomic regions were shown to be associated with AMH or AFP, and two genomic regions located on BTA1 (64.9-65.0 Mb and 109.1-109.2 Mb) overlapped between the traits. Various candidate genes were identified to be potentially linked to important biological processes such as ovulation, tissue remodeling, and the immune system. Our findings support the use of AMH and AFP as indicator traits to genetically improve fertility rates in Nellore cattle and identify better oocyte donors.
Keywords: anti-Mullerian; biomarker; fertility rate; indicine; GWAS; heritability; ovarian reserve; reproduction; Zebu